PENTINGNYA PENDIDIKAN INTERRELIGIUSITAS DI SEKOLAH DASAR - Dwi Hardianto, Paulus (P3TK, Sanata Dharma University, 2014)
In Indonesia, the last twenty years many cases had happened that caused disharmony. Some radical groups attacked different communities due to their different point of view. According to PPIMs research, not few teachers in Java have taught intolerance to their students. In this context, using a descriptive research with both qualitative and quantitative approaches (observation, questionnaire, and interview), the writer undertook a scientific research in some main Catholics schools in Jakarta e.g. Strada, Van Lith I Elementary School, Tarakanita V Elementary School, Melania II Elementary School and Budi Mulia Elementary School which have been trying to teach tolerance and pluralism to students. These Catholic schools had made a serious effort to incorporate the subject of tolerance and pluralism into their curriculum especially based on the thought of Jean Piaget, Lawrence Kohlberg, James W. Fowler as well as Gravissimum Educationis. From the result of this research, the writer is convinced of their contribution to peaceful coexistence in the country. Learning from them, the writer proposes again the importance of interreligious education in our pluralistic society.